External morphology of Chrysomya pinguis (Walker) (Diptera: Calliphoridae) revealed by scanning electron microscopy - Sukontason K. (2014)
The external morphology of the adult female blow fly, Chrysomya pinguis (Walker, 1858), was examined using scanning electron microscopy. Ultrastructure of the compound eye, ocellus, antenna, palpus, spiracles and portions of the thorax was highlighted. A great difference was observed in sculpture patterns of the corneal lens surface of the ommatidia of the compound eye and that of the ocelli, with the former being densely pustulate and the latter extremely sinuous. Several sensilla types were observed in this study including: sensilla chaetica, sensilla trichodea, sensilla basiconica and sensilla coeloconica. Their probable functions are discussed with reference to other literature. Morphological information about C. pinguis that was revealed in this study allows us to know such types of structures in much better detail and may eventually provide a basis for understanding some of the biological behavior of this fly species in the future. © 2007 Elsevier Ltd. All rights reserved.